Peran PGRI dalam Menghadapi Era Society 5.0 untuk Memulihkan Pendidikan di Indonesia (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2026)
The Society 5.0 era has brought significant changes to various aspects of life, including education. The rapid development of technology and science requires educators to adapt to changing conditions and develop competencies that are relevant to the demands of the times. In this context, the Indonesian Teachers Association (Persatuan Guru Republik Indonesia/PGRI) has an important role in supporting teacher professionalism and improving the quality of education in Indonesia. This article aims to examine the role of PGRI in facing the Society 5.0 era and its efforts to support the recovery and improvement of education in Indonesia. PGRI serves as a professional organization that encourages teacher competency development, career development, the use of technology in learning, and the strengthening of students’ character and 21st-century skills. In facing Society 5.0, teachers are required not only to master technology but also to develop creativity, critical thinking, communication, and collaboration skills while maintaining human values in the learning process. Therefore, PGRI needs to continuously support teachers through professional development, learning innovation, protection, and improved welfare so that teachers can perform their professional roles effectively amid changing educational demands.